Using Geographic Signatures as Query and Document Scopes in Geographic IR - Cardoso, Nuno (2012)
This paper reports the participation of the University of Lisbon at the 2007 GeoCLEF task. We adopted a novel approach for GIR, focused on handling geographic features and feature types on both queries and documents, generating signatures with multiple geographic concepts as a scope of interest. We experimented new query expansion and text mining strategies, relevance feedback approaches and ranking metrics.